SISTEM PAKAR MENGGUNAKAN FORWARD CHAINING DAN CERTAINTY FACTOR UNTUK DIAGNOSA KERUSAKAN SMARTPHONE - Yusra Fadhillah (Institut Pendidikan Tapanuli Selatan, 2020)
Through the passing of time the development of a smartphone increasing and facilities is many and it is developing , defects that occurred are also often occurs .So that the passenger crowds people to do service in various places .Expert system the diagnosis was undertaken with the aim to help the process the result the diagnoses damage to a smartphone so that they do not take a long time to make sure the result the diagnoses further .By using the method forward chaining and certainty factor , begins with information to in the form of real they were combined into a rule to produce a conclusion .The results of that which is inferred on a forward chaining and certainty factor could reach up to match the level of as much as 73,33 % compared with the result by renowned expert in .The number is already shows that this method suitable to help people.